Gedunin inhibits pancreatic cancer by altering sonic hedgehog signaling pathway - Subramani, Ramadevi (Oncotarget, 2016)
INTRODUCTION: The lack of efficient treatment options for pancreatic cancer highlights the critical need for the development of novel and effective chemotherapeutic agents. The medicinal properties found in plants have been used to treat many different illnesses including cancers. This study focuses on the anticancer effects of gedunin, a natural compound isolated from Azadirachta indica. METHODS: Anti–proliferative effect of gedunin on pancreatic cancer cells was assessed using MTS assay. We used matrigel invasion assay, scratch assay, and soft agar colony formation assay to measure the anti–metastatic potential of gedunin. Immunoblotting was performed to analyze the effect of gedunin on the expression of key proteins involved in pancreatic cancer growth and metastasis. Gedunin induced apoptosis was measured using flow cytometric analysis. To further validate, xenograft studies with HPAC cells were performed. RESULTS: Gedunin treatment is highly effective in inducing death of pancreatic cancer cells via intrinsic and extrinsic mediated apoptosis. Our data further indicates that gedunin inhibited metastasis of pancreatic cancer cells by decreasing their EMT, invasive, migratory and colony formation capabilities. Gedunin treatment also inhibited sonic hedgehog signaling pathways. Further, experiments with recombinant sonic hedgehog protein and Gli inhibitor (Gant-61) demonstrated that gedunin induces its anti–metastatic effect through inhibition of sonic hedgehog signaling. The anti–cancer effect of gedunin was further validated using xenograft mouse model. CONCLUSION: Overall, our data suggests that gedunin could serve as a potent anticancer agent against pancreatic cancers.